Christ in the tabernacle with some remarks on the offerings - White, Frank H. (London, UK S.W. Partridge, 1883)
Includes twelve chromo-lithographs as illustrations. Separate booklet included.
Keywords: Bible. O.T. Exodus -- tabernacle -- typology